New genus and species of Leptopsaltriini (Hemiptera: Cicadidae: Cicadinae) from China and Vietnam, with colour-changing behaviour reported for the first time in Cicadoidea - Wei, Cong; Wang, Siyue; Hayashi, Masami; He, Miao; Pham, Hong Thai (Zootaxa, 2020)
One new cicada genus Versicolora gen. nov. and two new species, V. ziyongi sp. nov. from China and V. bellula sp. nov. from China and Vietnam, are described. The new genus is placed in the tribe Leptopsaltriini of the subfamily Cicadinae. The relationship of this new genus to other related taxa is discussed. Versicolora ziyongi sp. nov. camouflages itself on the bark of the host-plants and gradually changes its body colour when captured. This colour-changing behaviour is recorded for the first time in Cicadoidea, which provides innovative information for ecomorphological study of this remarkable species and other cicadas that potentially exhibit this behaviour.